PENERAPAN MODEL COOPERATIF LEARNING TIPE NHT DALAM UPAYA PENINGKATAN HASIL BELAJAR - Tonggi Gurning (JURNAL PENA EDUKASI, 2019)
Abstract: Student learning outcomes by applying the Cooperative type NHT learning model to be increased. Before carrying out the action the average value of Mathematics subjects is 65.00 and standard deviation is 2.14. After taking action on the first cycle the average student learning outcomes value becomes 73.08 and standard deviation is 7.86. Likewise in the second cycle the average student learning outcomes increased by 81.25 in the good category with a standard deviation of 8.59. Before the category action was taken the average student learning outcomes were in the low category with a 50% completeness level (of 48 students who completed 24 people). In the first cycle after the action was carried out the student learning outcomes were in the medium category with a completeness level of 79.17% (38 people completed from 48 students). In the second cycle after further action was taken as a result of reflection of the first cycle of student learning outcomes in the high category with 100% completeness. Keyword: Learning Outcomes, NHT Abstrak: Hasil belajar siswa dengan menerapkan model pembelajaran Kooperatif tipe NHT menjadi meningkat. Sebelum dilaksanakan tindakan nilai rata-rata mata pelajaran Matematika adalah 65,00 dan standar deviasi 2,14. Setelah dilakukan tindakan pada siklus I nilai hasil belajar siswa rata-ratanya menjadi 73,08 dan standar deviasi 7,86. Demikian pula pada siklus II rata-rata hasil belajar siswa menjadi meningkat yaitu 81,25 berada pada kategori baik dengan standar deviasinya 8,59.Sebelum dilakukan tindakan kategori rata-rata hasil belajar siswa berada pada kategori rendah dengan tingkat ketuntasan 50 % (Dari 48 orang siswa yang tuntas 24 orang). Pada siklus I setelah dilakukan tindakan hasil belajar siswa berada pada kategori sedang dengan tingkat ketuntasan 79,17 % (38 orang yang tuntas dari 48 siswa). Pada siklus II setelah dilaksanakan tindakan lebih lanjut sebagai hasil refleksi siklus I hasil belajar siswa pada kategori tinggi dengan tingkat ketuntasan 100 %. Kata kunci: Hasil Belajar, NHT